2011
DOI: 10.1111/j.1365-2664.2011.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Using lichen functional diversity to assess the effects of atmospheric ammonia in Mediterranean woodlands

Abstract: Summary1. Atmospheric ammonia (NH 3 ) is one of the main drivers for ecosystem changes world-wide, including biodiversity loss. Modelling its deposition to evaluate its impact on ecosystems has been the focus of many studies. For that, universal indicators are needed to determine and compare the early effects of NH 3 across ecosystems. 2. We evaluate the effects of atmospheric NH 3 in ecosystems using lichens, which are one of the most sensitive communities at the ecosystem level. Rather than measuring total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 54 publications
4
78
1
2
Order By: Relevance
“…For correlating LDVs with [NH 3 ] atm , an interpolation of one of those variables was necessary, because they were not Species with * had their classification corrected after Pinho et al (2011). None of the species found is known to fix nitrogen.…”
Section: Critical Loads Of Nitrogen Deposition and Critical Levels Ofmentioning
confidence: 99%
“…For correlating LDVs with [NH 3 ] atm , an interpolation of one of those variables was necessary, because they were not Species with * had their classification corrected after Pinho et al (2011). None of the species found is known to fix nitrogen.…”
Section: Critical Loads Of Nitrogen Deposition and Critical Levels Ofmentioning
confidence: 99%
“…The sensitivity of terrestrial biodiversity to the deposition of oxidized and reduced N provides the basis for setting critical loads for N deposition both in Europe and North America (Cape et al 2009;Bobbink and Hettelingh 2011;Pinho et al 2011Pinho et al , 2012. Independently derived critical levels for lichens and moss diversity have been found to be similar for northern and southern Europe, thus emphasizing the universal applicability of these plant groups as ecological indicators of N deposition.…”
Section: Terrestrial Biodiversity Impactsmentioning
confidence: 99%
“…For example, some previous studies have suggested that very sensitive organisms, such as lichens and mosses, could be effective early-warning indicators of atmospheric Nr pollution in the early stages of anthropogenic disturbance of N cycles in an ecosystem (Pinho et al 2011). The functional diversity of lichens and/or mosses coupled with measures of their nitrogen content and isotopic composition has the potential to be explicit spatial indicators of the early effects of Nr pollution.…”
Section: The Need For International Integration Of Long-term Ecosystementioning
confidence: 99%
“…In this work, the dispersion and the distance of influence of eutrophication/NH 3 in lichens was found to be of short-range. However, the areas affected by it were found to be widespread in the territory, and always associated to agricultural sources (Pinho et al 2011(Pinho et al , 2012b.…”
Section: Why Do We Need To Understand Biosphere-atmosphere Interactions?mentioning
confidence: 99%
“…The green-algal lichens were positively related to potential solar radiation whereas cyanolichens were negatively related (Pinho et al 2010). It this study it has been proved that lichen communities can be used to: i) model long-term microclimatic conditions with high spatial resolution and ii) model the disturbance caused by neighborhood areas, even in natural parks with low-intensity human activities, for conservation purposes (Pinho et al 2011(Pinho et al , 2012a.…”
Section: Why Do We Need To Understand Biosphere-atmosphere Interactions?mentioning
confidence: 99%